Refugee crisis - casus of Cottbus - Kruk, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The fact that about 4000 immigrants are placed in Cottbus, situated 192 km from Poznań and 83 km from Zielona Góra, makes us feel it is necessary to analyze modus operandi of the entities legitimizing or delegitimizing the Open Door policy of the Chancellor Angela Merkel.
Keywords: refugee crisis; extremism